(untitled) (Acta Polytechnica CTU Proceedings, 2023)
HERA (High Burnup Experiments in Reactivity Initiated Accident) is one of the programmes which should replace closed Halden reactor. As the name implies HERA is focused on the tests simulated RIA (Reactivity Initiated Accident) and the aim of the programme is to investigate the performance and behaviour of high burnup fuel in RIA transients. The first phase of HERA programme consists of two steps which are the blind calculation of different RIA scenarios (different pulse width, enthalpy increase, hydrogen content and gap size) and in-reactor test with fresh fuel. The set of thermomechanical calculation was performed with the FRAPTRAN computer code as part of the first phase of HERA. The influence of several parameters on the fuel behaviour was observed, the varying parameters were the pulse width, peak radial average enthalpy increase, hydrogen content and the hydrogen rim size and gap size. In addition, the effect of type and setting of boundary condition was investigated.